The Role of Language Ideologies in Students’ Willingness to Communicate in English: A Case Study of Indonesian EFL Students - Fatimah, Umul; Sumardi, Sumardi; Putra, Kristian Adi (Universitas PGRI Adi Buana Surabaya, 2025)
This study aims to explore the role of language ideologies in students’ willingness to communicate (WTC) in junior high school students from Central Java. This study used a case study involving 91 ninth grade junior high school students from a state junior high school in Central Java. Data collection was carried out through questionnaires, observations, and interviews. From the questionnaire and interview results, several students from six classes were chosen through purposive sampling to join a classroom observation. The interviews were used to collect the main data focused on question-and-answer activities during lessons. The study results showed that most of the students see English as important for career and education, English as a symbol of social status, balancing global English and local cultural identity, and lack of confidence in language use. The role of language ideology in the class shows that students with positive language ideology have high willingness to communicate (WTC), whereas those with contradicting language ideology has low willingness to communicate (WTC). These results fit earlier research showing that WTC depends on students’ attitudes, emotions, and the classroom environment, and language ideologies alone aren’t enough. Students also need confidence, supportive teachers and peers, and plenty of low-pressure chances to practice.